Development of an RFID-based lane-level positioning system - Bautista, Brigitte Anne L.
Intelligent Transport Systems (ITS) aim to improve traffic conditions and reduce vehicular accidents by embedding technologies to vehicles and roadside infrastructures. As a research area under ITS, Lane Level Positioning (LLP) determines which lane a vehicle is taking at any period of time. Current LLP systems utilize image processing and the Global Positioning System (GPS). However, the said systems rely heavily on image sensors and highly accurate GPS receivers, whose cost and signal availability hinders it to be implemented on a wide-scale basis. In search of a low-cost alternative that will eliminate the shortcomings of previous implementations, the project aims to design and implement a high-frequency (HF) RFID-based lane level positioning system. The system is meant to be sufficiently accurate for lane-level positioning, and provide drivers with in-vehicle, real-time traffic and position information. The system was implemented by mounting an Hf reader with an output power of 120mW inside the vehicle, while the corresponding HF tags were placed on the road. To ensure successful reads, a 36 x 12 inch external loop antenna was mounted under the vehicle to maintain close proximity to the tags. A Zilog microcontroller development board was used to control the reader to issue inventory commands and receive the tag reply. The information that is received is then sent to a PC inside the vehicle for data display, as well as to a remote computer via Short Messaging Service (SMS) for vehicle monitoring. The system was first mounted on a trolley before being mounted on the vehicle to test its performance on slow speeds. The trolley-mounted system was made to run over 10 tags spaced 1.8 meters apart. Starting from 4 inches, the elevation of the antenna from the ground was increased by 2 inches after every trial, until the system registers a 0% read rate. The trolley tests using different antennas showed that the system can achieve a 90% read rate at 10 km/hr and a 6-inch antenna-to-tag distance. For the vehicle tests, the system was made to rune over 10 road tags spaced 4.5 meters apart. The vehicle tests showed that the system achieves a maximum hit rate of 80% at 5 kph and a minimum hit rate of 10% at 50 kph. Causes of unsuccessful reads may be attributed to cases wherein the antenna does not run directly over the tag, or to the delay incurred by sending information via SMS. By using readers with higher transmit power and larger antennas to maximize the chances of a tag being read the system looks promising as an alternative vehicle positioning system in moderate to high speeds. This could contribute immensely to existing literature on positioning systems and help improve existing implementations.